2006
DOI: 10.1097/01.hjh.0000242398.60838.5d
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure response to exercise in type 1 diabetes families compared with healthy control individuals

Abstract: An abnormal blood pressure response to exercise testing has been identified for the first time in asymptomatic normotensive non-diabetic relatives of type 1 diabetics, which was associated with indices of metabolic syndrome and oxidative damage. Moreover, in healthy normotensive non-diabetic control individuals (without a family history of type 1 diabetes), the systolic blood pressure response to exercise was significantly correlated with HbA1c levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Of the 47 studies reporting on adverse events or lack thereof, 22 (Knowler et al 2002;Gaudet-Savard et al 2007;Avery et al 1997;Baldi and Snowling 2003;Balducci et al 2004Balducci et al , 2006Honkola et al 1997;Inoguchi et al 2000;Irwin et al 2003;Konstantinidou et al 2002;Kouidi et al 2004;Lehmann et al 1997;Loimaala et al 2007;Maiorana et al 2002;Mosher et al 1998;Mourier et al 1997;Oh-Park et al 2002;Ozdirenç et al 2004;Tokmakidis et al 2004;Tudor-Locke et al 2004;Dunstan et al 2002) suggested (or stated implicitly) that they had no adverse events associated with the intervention (i.e., exercise testing and (or) training); 13 (Pan et al 1997;Agurs-Collins, Kumanyika et al 1997;Brankston et al 2004;Brandon et al 2003;Castaneda et al 2002;Cauza et al 2005;Dunstan et al 1997Dunstan et al , 1998Fuchsjäger-Mayrl et al 2002;Giannopoulou et al 2005;Ibañez et al 2005;Loimaala et al 2003;Matteucci et al 2006) provided information on drop out that appeared unrelated to any adverse event caused by exercise (for a total of ∼75% no adverse events); 6 (Bernbaum et al 1989;Schneider et al 1984;Banzer et a...…”
Section: Adverse Events Documentedmentioning
confidence: 99%
“…Of the 47 studies reporting on adverse events or lack thereof, 22 (Knowler et al 2002;Gaudet-Savard et al 2007;Avery et al 1997;Baldi and Snowling 2003;Balducci et al 2004Balducci et al , 2006Honkola et al 1997;Inoguchi et al 2000;Irwin et al 2003;Konstantinidou et al 2002;Kouidi et al 2004;Lehmann et al 1997;Loimaala et al 2007;Maiorana et al 2002;Mosher et al 1998;Mourier et al 1997;Oh-Park et al 2002;Ozdirenç et al 2004;Tokmakidis et al 2004;Tudor-Locke et al 2004;Dunstan et al 2002) suggested (or stated implicitly) that they had no adverse events associated with the intervention (i.e., exercise testing and (or) training); 13 (Pan et al 1997;Agurs-Collins, Kumanyika et al 1997;Brankston et al 2004;Brandon et al 2003;Castaneda et al 2002;Cauza et al 2005;Dunstan et al 1997Dunstan et al , 1998Fuchsjäger-Mayrl et al 2002;Giannopoulou et al 2005;Ibañez et al 2005;Loimaala et al 2003;Matteucci et al 2006) provided information on drop out that appeared unrelated to any adverse event caused by exercise (for a total of ∼75% no adverse events); 6 (Bernbaum et al 1989;Schneider et al 1984;Banzer et a...…”
Section: Adverse Events Documentedmentioning
confidence: 99%
“…We concluded that anthropometric and anamnestic data on child and family yield more accurate estimates of risk profile: fat distribution seems relevant for metabolic and cardiovascular disorders. Since our initial investigations on type 1 diabetes families, we found that first degree relatives' BMI tended to be higher when compared with healthy control subjects who had no first-degree relative with type 1 diabetes, although the difference did not always reach statistical significance (Matteucci & Giampietro, 2000a;Matteucci et al 2004aMatteucci et al , 2004bMatteucci et al 2006). In recent years, on the contrary, the difference in BMI between unaffected siblings of type 1 diabetic probands and healthy control subjects has reached the statistical significance ( Figure 1, .…”
Section: Body Weight In Type 1 Diabetes Familiesmentioning
confidence: 95%
“…We identified an abnormal blood pressure response to exercise testing not only in type 1 diabetic probands but also in asymptomatic normotensive non-diabetic relatives of type 1 diabetics, in which it was associated with indices of metabolic syndrome and oxidative damage. Furthermore, in healthy normotensive non-diabetic control subjects without family history of type 1 diabetes, strong associations were found 1) between resting systolic blood pressure and fasting plasma glucose as well as fasting plasma insulin levels, and 2) between systolic blood pressure response to exercise and HbA1c levels (Matteucci et al, 2006). In a recent study, we performed 24-hour ambulatory blood pressure monitoring in type 1 diabetes families with the primary aim of investigating the circadian variability of blood pressure and the ambulatory arterial stiffness index in healthy siblings of type 1 diabetes patients vs healthy control subjects who had no first-degree relative with type 1 diabetes .…”
Section: Familial Cardiovascular Abnormalitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, hypercoagulability is also linked to the metabolic syndrome, dyslipidemia, anaemia and even the hemodynamic response to exercise [201,[207][208][209]. It is also associated with a poorer outcome in coronary artery disease, heart failure and is correlated with the severity of target-organ damage including renal impairment [210][211][212].…”
Section: Underlying Pathologymentioning
confidence: 99%